2013
DOI: 10.5463/dcid.v24i1.191
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Education in Bangladesh: Are Pre-service Teachers Ready to Accept Students with Special Educational Needs in Regular Classes?

Abstract: Purpose: The aim of this study was to examine pre-service special education (PSpE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 29 publications
3
24
0
3
Order By: Relevance
“…A quarter of them agreed and over a quarter of them was undecided about these beliefs. The results are consistent with other findings indicating that university students in Ghana (Naami & Hayashi, 2012), most pre-service teachers in Botswana (Dart, 2006), teachers in United Arab Emirates (Gaad, 2004) and pre-service teachers in Bangladesh (Malak, 2013) are predisposed to misconceptions and superstitious beliefs about the causes of disability which influence them to worry about students with disabilities.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…A quarter of them agreed and over a quarter of them was undecided about these beliefs. The results are consistent with other findings indicating that university students in Ghana (Naami & Hayashi, 2012), most pre-service teachers in Botswana (Dart, 2006), teachers in United Arab Emirates (Gaad, 2004) and pre-service teachers in Bangladesh (Malak, 2013) are predisposed to misconceptions and superstitious beliefs about the causes of disability which influence them to worry about students with disabilities.…”
Section: Discussionsupporting
confidence: 82%
“…Conversely, increased contact with persons with disabilities has been found to explain positive changes in scores on comfort levels (Carroll, Forlin, & Jobling, 2003;Sharma et al, 2008). Pre-service teachers with a family member or close friend with a disability exhibit more positive attitudes towards students with disabilities (Haimour, 2012) and inclusion (Dart, 2006;Parasuram, 2006) and fewer concerns about the inclusion of students with disabilities into regular classes (Chhabra et al, 2010;Forlin et al, 2009;Malak, 2013).…”
Section: International Journal Of Research Studies In Education 57mentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies reported the positive effects of courses on inclusion and teaching children with SEN and some of them also described the content of those courses (e.g. O'Gorman & Drudy, 2011;Malak, 2013;Oswald & Swart, 2011;Ahsan, Sharma & Deppeler, 2012). Sparks (2009, p. 16) pointed out that "the most important issue masked by the use of course substitutions and waivers is that special educators and foreign language instructors feel no sense of urgency to develop teaching methods that can be used with at-risk learners".…”
Section: Review Of Literaturementioning
confidence: 99%